MyosinA is a druggable target in the widespread protozoan parasite Toxoplasma gondii. - Anne Kelsen; Robyn S Kent; Anne K Snyder; Eddie Wehri; Stephen J Bishop; Rachel V Stadler; Cameron Powell; Bruno Martorelli di Genova; Pramod K Rompikuntal; Martin J Boulanger; David M Warshaw; Nicholas J Westwood; et al. (PLoS Biology, 2023)
Toxoplasma gondii is a widespread apicomplexan parasite that can cause severe disease in its human hosts. The ability of T. gondii and other apicomplexan parasites to invade into, egress from, and move between cells of the hosts they infect is critical to parasite virulence and disease progression. An unusual and highly conserved parasite myosin motor (TgMyoA) plays a central role in T. gondii motility. The goal of this work was to determine whether the parasite's motility and lytic cycle can be disrupted through pharmacological inhibition of TgMyoA, as an approach to altering disease progression in vivo. To this end, we first sought to identify inhibitors of TgMyoA by screening a collection of 50,000 structurally diverse small molecules for inhibitors of the recombinant motor's actin-activated ATPase activity. The top hit to emerge from the screen, KNX-002, inhibited TgMyoA with little to no effect on any of the vertebrate myosins tested. KNX-002 was also active against parasites, inhibiting parasite motility and growth in culture in a dose-dependent manner. We used chemical mutagenesis, selection in KNX-002, and targeted sequencing to identify a mutation in TgMyoA (T130A) that renders the recombinant motor less sensitive to compound. Compared to wild-type parasites, parasites expressing the T130A mutation showed reduced sensitivity to KNX-002 in motility and growth assays, confirming TgMyoA as a biologically relevant target of KNX-002. Finally, we present evidence that KNX-002 can slow disease progression in mice infected with wild-type parasites, but not parasites expressing the resistance-conferring TgMyoA T130A mutation. Taken together, these data demonstrate the specificity of KNX-002 for TgMyoA, both in vitro and in vivo, and validate TgMyoA as a druggable target in infections with T. gondii. Since TgMyoA is essential for virulence, conserved in apicomplexan parasites, and distinctly different from the myosins found in humans, pharmacological inhibition of MyoA offers a promising new approach to treating the devastating diseases caused by T. gondii and other apicomplexan parasites.